Synthesis of new Schiff base and its Ni(II), Cu(II), Zn(II) and Co(II) complexes; photophysical, fluorescence quenching and thermal studies - Karaoglan, Gulnur Keser (ELSEVIER, 2022)
In this study, a new Schiff base ligand, that was obtained from the condensation reaction of 1,10-phenanthrolin-5-amine with 4-fluorobenzaldehyde, and its novel stable series of Schiff base metal complexes ( M = Ni(II), Cu(II), Zn(II), Co(II)) were synthesized in suitable conditions to contribute to increase anticancer drug activity in drug transport systems. The new compounds have been characterized using FT-IR, UV-Vis, H-1 NMR, LC-MS and elemental analysis. The thermal stabilities of these complexes were studied by applying thermogravimetric (TGA/DTA) and the related decomposition steps were investigated. The TGA measurements were carried out to determine the effect of metals on the thermal strength of the newly synthesized complexes. The Cu(II) complex exhibited higher thermal strength. The photophysical properties of the Schiff base ligand and its metal complexes were studied in different solvents such as DMF, DMSO, methanol and ethanol. Dynamic quenching constant (K-SV) values of the compounds as important parameters for biological systems in fluorescence quenching studies were calculated and the highest K-SV value (17.42) was obtained for compound 6 in DMSO, however, the highest K-SV value (7.80) was determined for compound 3 in DMF. The K-SV values of the Schiff base ligand and its zinc complex were higher than those that have been reported in the literature. Due to the high K-SV values of these compounds ( 3 and 6 ), they can be listed as anticancer drug active ingredients in drug transport systems. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: Schiff base complexes; 1,10-phenanthrolin; Photophysical; Fluorescence; Quenching; LUMINESCENCE PROPERTIES; ANTIMICROBIAL ACTIVITY; DERIVATIVES; METAL; CATALYSTS; BEHAVIOR; LIGANDS; Chemistry